Comprehensive QoS analysis of MIPL based mobile IPv6 using single VS. dual interfaces - Uddin, Mohammad Moshee; Haseeb, Shariq; Ahmed, Mohiuddin; Pathan, Al-Sakib Khan (2011)
Mobile nodes with dual interfaces are not very common and not many studies have been done in this area. In this work, we have done a comprehensive study of dual interfaces on a test-bed to find out the effectiveness of dual interfaces and compared the results with single interface. We have implemented an MIPL based test-bed to study the QoS parameters, which affect mobile nodes, and are considered to be of paramount importance in real time application running on MIPv6 mobile nodes. The hand-off latency, packet loss, data throughput and jitters are the parameters we have considered in this research. Finally, we show a comparison of performance between dual interfaces and single interface on a mobile node.